Dibattito tra Massimo Fagioli e un gruppo di architetti dell’Analisi collettiva - Vari, Autori (Il sogno della farfalla, 2025)
This article presents the dialogue between Massimo Fagioli and a group of architects from the Collective Analysis (Analisi collettiva), conducted in October 1994 on the occasion of the exhibition “Il coraggio delle immagini” in Tunis, which explored the intersection of psychiatry, creativity, and architectural design through the lens of the Human Birth Theory. In an open exchange, the participants reflect on the role of internal images, the relationship between artistic intuition and functional structure, and the transformative potential of collaborative processes that transcend conventional academic approaches. The conversation emphasizes a shared pursuit of a creative practice capable of modifying reality without destruction, one rooted in artistic vision and human relationships.